“Why can’t Johnny write? He sounds okay!” Attending to form in English second language teaching - Ayliff, Diana (Faculty of Education, University of the Free State, 2010)
This article addresses the problem of poor written English amongst many South African learners who study English as their First Additional Language (FAL) at secondary school level, and the effect this has on their tertiary education and their future careers. The reasons for this poor mastery of written discourse are explored and, in particular, it is argued that the problems that have arisen are because of the communicative meaning-focused approach that has been the raison d’être of the second language syllabi for many years. This approach has also underpinned the OBE curriculum for English as FAL. An alternative method, in which the form of the language is focused upon, is explored and it is argued that this methodology would be a more successful one for South African learners and go a long way to solving the problem of the poor standard of English of matriculants.
Keywords: English second language; Communicative language teaching; Form-focused instruction